Harmoni Dalam Keberagaman; Analisis Sikap Menghormati Hari Raya Nyepi Melalui Pengurangan Suara Adzan dan Berjalan Kaki Menuju Masjid Di Bali - Urfi Ainu Syirwan Rita Rahayuningsih, Muhammad Junaidi (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
This study examines the praxis of religious moderation as a fundamental pillar of social harmony in Bali, focusing on the adaptive attitudes of the Muslim community in Patas Village, Gerokgak District, Buleleng Regency, during the celebration of the Hindu Day of Silence (Nyepi). This qualitative case study aims to analyze the specific contributions of the Muslim community namely, adjusting the volume of the Adzan (call to prayer) and limiting the use of vehicles by walking to the Jami’ Nurul Falah Mosque in strengthening tolerance and interreligious harmony. The research employs C. Otto Scharmer’s U-Model analytical framework to map the collective transformation processes underlying these adaptive practices. The findings indicate that the harmony achieved in Patas Village is the result of a shared awareness rooted in the local value of Menyama Braya (kinship and togetherness) and grounded in the theological principle of Ushul Fiqh al-‘adatu al-muhakkamah (custom as a legal consideration). This transformative process moves from Downloading (the habitual practice of using full-volume loudspeakers during prayer) to Realizing (a new adaptive behavior) through Presencing, in which symbolic acts of sacrifice such as lowering the Adzan volume and walking instead of driving are accepted as manifestations of collective sincerity, as agreed upon by the Interfaith Harmony Forum (FKUB). These practices are also perceived as not diminishing the solemnity of worship. Such simple yet meaningful actions create a high-trust equilibrium, serving as an effective mechanism for conflict prevention. This study fills a gap in the existing literature by presenting a concrete model of tolerance that emerges from social interaction and the collective transformation of consciousness within a minority community in respecting the traditions of the majority.